1982
DOI: 10.1136/jnnp.45.7.577
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Parkinson's disease.

Abstract: In a case control study of the relationship between smoking habits and Parkinson's disease a negative association was demonstrated with a relative risk of 0-52. A history of smoking up to 20 years earlier was associated with a risk of developing Parkinson's disease equal to about half that in non-smokers. The type of disease, age of onset and rate of progression were associated with a similar reduction in risk implying that in respect of smoking history the disease is homogeneous. The positive correlation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
1
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(44 citation statements)
references
References 8 publications
6
35
1
2
Order By: Relevance
“…Although many of the case-control studies reported ORs below unity, the association was nonsignificant in most studies [142,143,293,298,303,309,310,380,407,408,410,413,415,423]. A Swedish study that investigated the relationship of PD with beer, wine, and liquor reported inverse associations for each of these types of alcoholic beverages in univariate analyses.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Although many of the case-control studies reported ORs below unity, the association was nonsignificant in most studies [142,143,293,298,303,309,310,380,407,408,410,413,415,423]. A Swedish study that investigated the relationship of PD with beer, wine, and liquor reported inverse associations for each of these types of alcoholic beverages in univariate analyses.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…The negative association between PD and tobacco use has been noted in previous studies. 38 " 40 It remains unexplained, but several hypotheses have been suggested, 541 including smoking-facilitated dopamine release. 42 In view of the experimental evidence linking dopamine release to ischemic cerebral damage, it is interesting to speculate whether this enhanced release is still one more way in which tobacco use predisposes to the development of clinically apparent stroke.…”
mentioning
confidence: 99%
“…This particular relation is first alluded to by Kahn 12 in 1966 and has held true in several other studies. 1 - 41314 Baron 15 reports that smoking may actually be a protective exposure in relation to developing PD. Smoking facilitates dopamine release and dopaminergic neural transmission throughout the nervous system, which could delay or prevent the emergence of the clinical symptoms of PD in subjects whose dopaminergic functioning would otherwise drop below a symptom threshold.…”
Section: Cumulative Incidence = Pd Patients Controlsmentioning
confidence: 99%
“…Atherosclerosis has been suggested as a possible cause of PD by some authors and dismissed as a possible cause by others. 1 Degenerative cerebrovascular disease and PD afflict similar age groups, and some manifestations of cerebral atherosclerosis may be clinically difficult to distinguish from those of PD.…”
mentioning
confidence: 99%